An energy model of 4G smartphone oriented towards typical network applications. (2018) - Liu, Tundong; Lin, Yun; Xu, Zhuobin; Xie, Yi; Chen, Fufeng; Xue, Guozhi
4G has achieved considerable success because of its high data rate. But the short battery lifetime of mobile devices hinders the development of 4G. To improve energy efficiency, much effort has been made to study the process of energy consumption in smartphones. Some hardware-based methods, using expensive instruments, are correct but unhandy. Some software-based methods are flexible, but incorrect, because they often omit the influence from communication performance. This paper proposes a smartphone energy model where typical applications (HTTP and FTP) and the wireless traffic data flow are considered. Experimental results show that the energy model accurately estimates the smartphone energy consumption in one operation of the application, whose accuracy rate is higher than 90%. This work is the first step toward the development of a new software-based method, which accurately estimates smartphone energy consumption.